Studi Pengaruh Penambahan Kerang Hijau (Perna Viridis) sebagai Material Akustik pada Kemampuan Absorbsi Bunyi: Susilo Indrawati - Susilo Indrawati, Susilo Indrawati (Jurnal Fisika dan Aplikasinya, 2025)
Green mussel (Perna viridis) is known as Green Shell, which has wide distribution in nearly all layers of the world. However, the potential of green leather shells have not been optimally used. Based on data from Indonesian exports of fishery products in 2003 and 2004, It’s commodities produced approximately 2,752 tonnes. The result of Activity on unit processing the green mussel is the solid cesspit very high. So, there are needed effort to use it and reduce negative impacts on human health and the environment. Remember that the shells have a lot of calcium, so in this study will be conducted early studies about the effect of green mussels for ability an accoustic material to absorb sound. The method is using the impedance tube. The materials used are white cement, gypsum, foam agent and powder leather shells.The result from the measurement of the percentage ratio green leather shell: white cement: gypsum 4: 0: 2 (270 gr green leather shell, no white cement, gypsum 135 gr) has changes of value the greatest of absorption coefficient.